Implementasi Pendidikan Karakter Disiplin dalam Pembelajaran PPKn di Sekolah Menengah Pertama - Erin Sulialfianti; Eky Risqiana (Faculty of Teacher Training and Education of Undaris, 2026)
This study aims to describe the implementation of discipline character education in Civics (PPKn) learning at Junior High Schools. Discipline character education is one of the core values that must be instilled in students as a foundation for building a nation of strong character. The research method used is descriptive qualitative research with data collection techniques through observation, in-depth interviews, and document study. Research subjects are PPKn teachers, school principals, and students. The results show that the implementation of discipline character education is carried out through three main channels: (1) integration in the classroom learning process, (2) habituation through school activities, and (3) exemplary behavior of teachers and educational staff. Obstacles found include inconsistency in rule enforcement, family environmental influences, and the impact of digital technology. Supporting factors include the principal's commitment, parental support, and positive school culture. This research recommends the need for synergy between school, family, and community in forming students' discipline character holistically and sustainably.Keywords: character education, discipline, PPKn, junior high school, implementation